The Students’ Perceptions of the Asynchronous Online Learning Model at Institut Parahikma Indonesia Post-Pandemic Covid-19 - Trisnawati, Ice; Nur, Sahril; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2023)
The objectives of the research were to discover students' perceptions of the asynchronous online learning model at Institut Parahikma Indonesia. The researcher applied phenomenological design in this research. Data obtained from the semi-structured interviews regarding the student’s perceptions of the asynchronous online learning model at Institut Parahikma Indonesia There were seven respondents, three males and four females in the Institut Parahikma Indonesia. They were selected by convenience sampling. The results of this study revealed the students' perceptions of the asynchronous learning model. Trough the interview mentioned several facts that the asynchronous learning model is attractive in learning model because of flexible, and useful, leaving traces and discipline learning models.